The Legal Conundrum Of Non-Interest Banking. A Case Study Of Islamic Bank In Nigeria. - Nabiebu, Miebaka; Takim Otu, Michael (International Journal of Scientific Research and Management (IJSRM), 2019)
The issuance of license to Jaiz bank plc as the first full-flesh Islamic bank in Nigeria to carry on Non-interest banking has generated heated debate among scholars, jurist, religious leaders and public commentators in Nigeria. Chiefly among these debate borders on the constitutionality of Non-interest (Islamic) banking in Nigeria; whether or not Islamic banking is established with the aim of Islamizing the entire Nigeria and whether or not it is meant to discriminate against Non-Muslims in Nigeria. Consequently, this work seek to appraise the legal conundrum or constitutionality of Islamic banking in Nigeria with a view to ascertaining whether or not Islamic banking is meant to Islamize Nigeria or it is meant to discriminate against non-Muslims. However the outcome of this research article shows that Islamic (Non- interest) banking is constitutional and is not meant to discriminate against Non- Muslims or Islamize Non-Muslims. Rather with the practice of dual banking (interest and non interest banking) in Nigeria, Nigerians would have the advantage of having different credit choices, the Nigerian banking sector would be more competitive thus enhance quality services, creation of more employment opportunities and would give the Nigerian government the opportunity to secure non-interest loan from Islamic development fund available globally to finance infrastructural projects. This work further concludes that the major challenge this banking system is facing in Nigeria is lack of adequate awareness about the operation of the banking system and lack of robust legal framework to adequately regulate the system. It is therefore suggested that a more comprehensive legal framework should be enacted by the Nigerian National Assembly to appropriately regulate the non-interest banking sector as well as creation of more awareness about the operation of the system through the social media, town hall meetings, newspapers and radio commentaries.